Reflection in Speech of the Individual-Typological Features of Language Personality - Наталія Фоміна (Психолінгвістика, 2019)
Introduction. The article is devoted to the actual psycholinguistic problem of reflecting in the various parameters of speech the features of a linguistic personality. Since speech is a unity of social, i.e. language as a sign system, and a unique individual – a subjective form of reflection of the objective reality and the way of formation and formulation of thought (Winter), which is determined by the motivational, dynamic, emotional, regulatory, cognitive characteristics of a linguistic personality, according to the author, a holistic study of all its stable communicative-speech and psychological properties, include their individual typological manifestations. The article presents the results of empirical studies of manifestations in speech of the individual typological features of various aspects of a linguistic personality, performed by N.A. Fomina and under her leadership, which allows to give a full and deep description of the personality.